Application of differential equation in L-R and C-R circuit analysis by classical method - Regmi, Rajendra Prasad (Janapriya Journal of Interdisciplinary Studies, 2017)
The paper deals with the analysis of L-R and C-R circuit by using linear differential equation of first order. A circuit containing an inductance L or a capacitor C and resistor R with current and voltage variable given by differential equation. The general solution of differential equation have two parts complementary function (C.F) and particular integral(P.I) in which C.F. represent transient response and P.I. represent steady response. The general solution of differential equation represent the complete response of network. In this connection, this paper includes L-R, C-R circuit and ordinary differential equation of first order and its solution. Janapriya Journal of Interdisciplinary Studies, Vol. 5 (December 2016), page: 114-123